Endocannabinoid system components as potential neuroimmune therapeutic targets in tinnitus - Bhat, Vishweshwara; Onaivi, Emmanuel Shan; Sharma, Venkatanarayanan (Frontiers in Neurology, 2023)
Research interest in understanding tinnitus has increased severalfold in the last decade to find a cure for this auditory disorder. Hyperacusis can also accompany tinnitus, although the mechanisms involved in hyperacusis and tinnitus are different. Millions of people suffer from some degree of tinnitus with hearing loss. Tinnitus is believed to be a form of sensory epilepsy, spawning neuronal hyperactivity from the cochlear nucleus and inferior colliculus of the auditory brainstem region. Cannabis has been used for recreation, medicinal purposes, and served as an entheogen from time immemorial. With the current and increasing global medical and recreational cannabis legalization, there is renewed enthusiasm for the use of cannabinoid drugs, and the role of the endocannabinoid system (ECS) in several health disorders including tinnitus which is associated with COVID-19. The ECS signaling pathways have been proposed to affect the underlying pathophysiology of tinnitus. Cannabinoid receptors (CBRs) have been found in the auditory system, raising interest in ECS signaling in hearing and tinnitus. However, previous studies mostly in animal models of tinnitus did not investigate the involvement of CB2Rs but focused on CB1R-based responses, which suggested that CB1R ligands had no effect and may even be harmful and worsen tinnitus. With new molecular techniques and transgenic approaches used to dissect the complexity of the ECS, the role of ECS/CB2R neuroimmunological function in the auditory system and tinnitus is emerging. This perspective proposes the role of emerging neuroimmune crosstalk of the ECS in sound-sensing structures of the auditory system as a potential pharmacogenomic therapeutic target using cannabinoid CB2R ligands in tinnitus in the era of the COVID-19 pandemic.